El comercio electrónico y su incidencia en el crecimiento financiero de los emprendedores del Cantón Quevedo, año 2023 - Llaguno Vásquez , Damaris Lisseth (2024)
The research addressed links elements of notable importance, e-commerce and entrepreneurs, considering the aspects related to this modern business model that provides multiple facilities for those who use it. The objective of the research is to evaluate the impact of e-commerce on the financial growth of entrepreneurs, as well as the acceptance that e-commerce receives from this public and the use they give it for the execution of their commercial activities. The development of this research is located in the urban area of the Canton Quevedo, Province of Los Ríos, the target population is the entrepreneurs of said environment. The research methodology to be followed is qualitative, applying an interview to a professional in the area, and quantitative, through a survey directed to entrepreneurs, under a sample of 363. The results were compiled in an Excel spreadsheet, the data processing, including tables and graphs, was carried out in the statistical program SPSS 29.02. These showed that entrepreneurs frequently use e-commerce, in fact, inherent results are obtained in strategic approaches in relation to marketing techniques when proposing the use of technological methods adopting a new way of marketing.